The potential use of Apgar score and neonatal encephalopathy in registry based studies - Dag Moster; Trond Markestad (Norsk Forening for Epidemiologi, 2007)
We have previously described the impact of Apgar scores on later major and minor disabilities. According to these and other studies, children with low Apgar scores have to show symptoms of neonatal encephalopathy in the first week of life to be at risk of developing later disabilities. Information on neonatal encephalopathy has traditionally been less accessible than Apgar scores in The Medical Birth Registry of Norway (MBRN). In the present study the possibility of extracting information on neonatal encephalopathy from the new notification form to the MBRN, which was introduced in late 1998, was investigated. The introduction of specific and generally accepted definitions of neonatal diagnoses combined with more comprehensive reports to MBRN from the neonatal departments may render registry based studies on neonatal encephalopathy possible in the future.